Transferability of weakest link model parameters of polysilicon from indentation fracture to failure of MEMS structures. (September 2021) - Satheesh, S.M.; Banerjee, Anuradha; Bhattacharya, Enakshi
Highlights: Bending tests were carried out on notched polysilicon micro-cantilevers till catastrophic failure. Finite element model for the fabricated cantilevers were developed and used for estimation of failure probability using weakest link theory. Influence of fabrication and geometric details like undercut and sidewall roughness on failure load were studied. Failure probability of tested structures were generated and predicted failure load is validated with experimental data. Abstract: Polysilicon weakest link model parameters obtained from indentation fracture are used to predict failure in MEMS structures. Plain and notched polysilicon micro-cantilevers were fabricated using surface micro-machining and bending tests were carried out till the structure failed catastrophically. To estimate the failure probability of fabricated samples, numerical studies were carried out on models closer to the actual experimental condition, by estimating and incorporating fabrication details such as undercut and roughness. Initially, the undercut inherent to fabrication process was estimated on plain cantilevers by comparing the elastic behavior with experiments. The geometry of open cavities in the sidewall, formed as a consequence of etching, were characterized using SEM micrographs. The stress field obtained from 3D FEM analysis of the notched geometries, including these geometric details, showed great sensitivity to the positioning of cavities in the sidewall relative to the top surface. Applying weakest link theory based local criteria, the probability distribution of failure load of tested structures was generated using weakest link parameters from indentation fracture. Failure loads, thus predicted, were validated with experimental data.